Comparison of the efficacy of topical heparin quick penetrating solution and intravenous hydrocortisone in the prevention of thrombophlebitis: A randomised controlled study - Tappa Rabbani; Muralikrishna Dommeti; Dakshinamurthy Gayathri; Ramachandran Gopinath; Gaddati Dedeepya (Journal of Clinical and Scientific Research)
Background: Superficial thrombophlebitis is a common complication associated with intravenous (IV) cannulation. We compared the efficacy of topical heparin quick penetrating solution (QPS) and IV hydrocortisone in the prevention of superficial thrombophlebitis. Methods: One hundred and sixty-five patients scheduled for surgery under regional anaesthesia were included in the study and randomised into three groups to receive topical QPS heparin (Group TH), IV hydrocortisone (Group IH) and neither topical QPS heparin nor IV hydrocortisone (but received saline as control) (control group) every 8 h for 24 h. Once the drug was applied topically or given IV, this time was noted as 0 h and monitored at 8 h, 16 h, 24 h and 48 h for the features of thrombophlebitis using a visual infusion phlebitis scale. Results: At 8 h, 16 h, 24 h and 48 h, both IV hydrocortisone and topical QPS heparin showed a significant reduction in thrombophlebitis incidence compared to the control group (P < 0.05). The mean rank-sum in Group TH at 8 h, 16 h, 24 h and 48 h (52.5, 53.5, 52.5 and 53.5) were significantly lower compared to Group IH (58.5, 57.5, 58.5 and 57.5) suggesting a high efficacy in the prevention of superficial thrombophlebitis with topical QPS heparin (P < 0.05). Conclusions: Both topical QPS heparin and IV hydrocortisone were effective in preventing superficial thrombophlebitis as compared to the control group; however, topical QPS heparin was more effective. Clinical Trial Registry of India No. CTRI/2023/04/051656.